A decacobalt(ii) cluster with triple-sandwich structure obtained by partial reductive hydrolysis of a pentacobalt(ii/iii) Weakley-type polyoxometalate. Issue 90 (24th October 2016) - Duan, Yan; Clemente-Juan, Juan M.; Fierro, José L. G.; Giménez-Saiz, Carlos; Coronado, Eugenio
Abstract : A new triple-layered decacobalt sandwich polyoxometalate has been obtained by partial reductive hydrolysis of an asymmetric pentacobalt polyoxometalate with hydrazine. Abstract : Partial reductive hydrolysis of a penta-Co II/III cluster [CoII4(H2 O)2 (Co III W9 O34 )(PW9 O34 )] 12− (1 ) leads to the formation of [Co2 Co3 (H2 O)(Co(OH)2 W7 O26 )(PW9 O34 )2 ] 22− (2 ). This polyoxometalate is made up of two capping [PW9 O34 ] 9− units and two bridging [W7 O26 ] 10− units that assemble to encapsulate a novel deca-Co II cluster core comprising octahedral and tetrahedral Co II ions.